Effect of Ferula communis L. on reproductive parameters in Awassi ewes - ONAL, A.G. (Journal of the Hellenic Veterinary Medical Society, 2019)
Nutrient composition of the diet affects follicular activity, embryonic development and reproductive hormones in ruminants. The objective of the present study was to investigate the effects of Ferula communis L. on some reproductive parameters of Awassi sheep. The experiment was carried out on 29 (15-16 months old) Awassi ewes. All ewes were allocated to receive either a control (14% CP and 11.7 MJ ME/kg, n=9) or a diet supplemented with 5% (75g, n=10) or 10% (150g, n=10) powdered F. communis root, respectively for 21 days. Oestrus was synchronized using intravaginal sponges, while oestrus behaviour was observed 24, 36 and 48h after the sponge removal. Blood samples were collected for the assessment of oestradiol and LH. At the end of the 21-day period, animals were slaughtered and ovarian structures were recorded. Corpora lutea tissues were cultured in vitro, and progesterone production was measured. The results indicate that the treatment of animals with 5% of F. communis root increased the percentage of animals in heat (80%, 60% and 10% for 5C, 10C, and the control group, respectively). Furthermore, the number of small follicles (1-3 mm) in treated groups was significantly higher than those of the control group. Moreover, the number of large follicles (>4 mm) in the control group was higher than those of the treatment groups. Plasma concentration of oestrogen and LH peak were similar in the control and treatment groups. Progesterone production by luteal cells cultured in vitro was higher for both treatment groups compared to the control. Herewith, supplementation of the diet of Awassi Sheep with F. communis root during the breeding season may enhance ovulation rate and luteal activity.